Foam Glass Gravel Experimentally Made in a 10 kW-Microwave Oven - Lucian Paunescu; Sorin Mircea Axinte; Felicia Cosmulescu (Journal La Multiapp, 2021)
Abstract The experimental manufacture of foam glass gravel from glass waste has been quantitatively extended by increasing the power of the microwave oven from 0.8 to10 kW, the authors' interest being focused on the quality of the foamed product. The work equipment was rather improvised, the existing used oven not being adequate except to small extent for the requirements of the experiment, but it allowed obtaining a product similar to those industrially manufactured by conventional techniques. Using a recipe previously tested on the 0.8 kW-microwave oven composed of 1 wt.% glycerol as a liquid foaming agent together with 8 wt.% water glass as an enveloping agent and 8 wt.% water as a binder, the main features of the foam glass gravel lumps were: bulk density of 0.22 g/cm3, porosity of 88.9%, thermal conductivity of 0.057 W/m·K, compressive strength of 5.9 MPa and pore size between 0.10-0.30 mm. The specific energy consumption was negatively influenced by the excessive internal volume of the oven, but even under these conditions its value was relatively low (between 1.53-1.69 kWh/kg).